2021
DOI: 10.1007/s00382-021-05917-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging new climate extremes over Europe

Abstract: Human society and natural systems are intrinsically adapted to the local climate mean and variability. Therefore, changes relative to the local expected variability are highly relevant for assessing impact and planning for adaptation as the climate changes. We analyse the emerging climate signal relative to the diagnosed internal variability (signal-to-noise ratio, S/N) of a set of recently published climate indices over Europe. We calculate the signal-to-noise ratio with respect to a recent baseline (1951–198… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…Furthermore, for warm and cold extremes that display larger variability, the signals for these indices tend to emerge later over both the tropics and extratropics (e.g., King, Donat, et al., 2015; Tan et al., 2018) relative to mean temperature. Currently, most studies on TOE have been conducted at global levels, with less detailed analyses over smaller scale regions (e.g., Batibeniz et al., 2020; Gaetani et al., 2020; Ossó et al., 2021), especially for Australia (King, Donat, et al., 2015). Under different future scenarios, we aim to investigate the TOE of extreme temperatures over Australia at the subregional scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for warm and cold extremes that display larger variability, the signals for these indices tend to emerge later over both the tropics and extratropics (e.g., King, Donat, et al., 2015; Tan et al., 2018) relative to mean temperature. Currently, most studies on TOE have been conducted at global levels, with less detailed analyses over smaller scale regions (e.g., Batibeniz et al., 2020; Gaetani et al., 2020; Ossó et al., 2021), especially for Australia (King, Donat, et al., 2015). Under different future scenarios, we aim to investigate the TOE of extreme temperatures over Australia at the subregional scale.…”
Section: Introductionmentioning
confidence: 99%
“…TOE is defined as the time when the externally forced climate signal (i.e., forced response) emerges from the noise (i.e., natural variability), suggesting that a significant change is detected and a novel climate regime becomes evident (e.g., Hawkins & Sutton, 2012; Hawkins et al., 2020; King, Donat, et al., 2015). Estimating TOE can provide insights for mitigation strategies, adaptation planning, and scientific community, as the forced response relative to the background noise may be more relevant for the assessment of climate impacts, compared to the absolute change (Beaumont et al., 2011; Deutsch et al., 2008; Hawkins & Sutton, 2012; Hawkins et al., 2020; Ossó et al., 2021). For example, similar absolute changes in extreme temperature can result in different ecological impacts since extratropical ecosystems are usually more resilient than tropical ecosystems, as they are adapted to a more variable climate (Beaumont et al., 2011; Deutsch et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of Lukić et al [8], the annual total precipitation (when it exceeds the 95th percentile (R95p)) is increasing in the investigated area, except for the Budapest meteorological station. Ossó et al [95] revealed that from 2000 to 2016, annual values of the R95p index were 5% larger in central Europe. The authors stated that, during the winter season, R95p was positive for most of Europe, thus leading to unusually intense winter precipitation.…”
Section: North Atlantic Oscillation Impactmentioning
confidence: 99%
“…As examples of such studies, Giorgi and Bi (2009) and Nguyen et al (2018) found in successive generations of GCM projections that in some high latitude regions, Asian regions and the Mediterranean the mean precipitation change signal emerged in the first half of the 21st century. Focusing on a number of extreme event indicators, studies such as those of Diffenbaugh et al (2017), Giorgi et al (2019), Hawkins et al (2020) and Osso et al (2021) found that global warming can lead to the occurrence of temperature and precipitation extremes of unprecedented intensity, in some cases already in the observed record of the late 20th and early 21st century.…”
Section: Introductionmentioning
confidence: 99%